Farnesol Decreases Biofilms of Staphylococcus epidermidis and Exhibits Synergy with Nafcillin and Vancomycin - Pammi, Mohan (2011)
Biofilm infections are frequently caused by S. epidermidis, are resistant to antimicrobial agents and adversely affect patient outcomes. We evaluated farnesol, the Candida quorum sensing molecule, on S. epidermidis biofilms, in vitro and in vivo. We evaluated ED(50), ED(75) and ED(90) –(drug concentrations causing 50%, 75% and 90% inhibition respectively) of farnesol and evaluated synergy with nafcillin and vancomycin. Farnesol’s effects on morphology of S. epidermidis biofilms were analyzed using confocal microscopy and real-time changes using a bioluminescent strain of S. epidermidis, Xen 43. In mice, effects of farnesol treatment on subcutaneous catheter biofilms, cultures of blood, kidney, catheter and peri-catheter tissues and bioluminescence in strain Xen 43 were evaluated. Farnesol inhibited biofilms (ED(50) ranged from 0.625 to 2.5 mM) and was synergistic with nafcillin and vancomycin at most combination ratios. Farnesol significantly decreased biovolume, substratum coverage and mean thickness of S. epidermidis biofilms. In mice, farnesol significantly decreased viable colony counts of S. epidermidis from blood, kidney, catheter and peri-catheter tissues and decreased Xen 43 bioluminescence. We confirmed the anti-biofilm effects of farnesol both in vitro and in vivo, in a bioluminescent strain and its synergy with antibiotics. Farnesol may be effective against clinical S. epidermidis biofilm infections.